Reflection as the Homebase of Teacher Education - Susanto, Andrias Tri (Beyond Words, 2015)
Abstract Reflection is widely accepted as a process to support, or even underlie, teacher education. However, the concept holds several confusions among education experts and practitioners. This article would then attempt to explain some confusing terms by reviewing relevant literature on this issue and to provide discussions on the benefits and challenges of reflection manifested in various options of reflective practicum. Keywords: Reflection, teacher education, reflective practicum